Patient reported outcomes in the FDA approved drugs for systemic rheumatic diseases (2013–2024) - Yan Xie; Yang Liu; Yunhe Qin; Geng Yin; Xiaoyuan Chen; Qibing Xie (Health and Quality of Life Outcomes)
Abstract Background Patient-reported outcomes (PROs) in systemic rheumatic diseases (SRDs) are in the forefront of clinical research. However, a comprehensive evaluation of PROs in pivotal trials supporting SRD drug approval is lacking. Objective This study aims to systematically characterize the use of PROs in pivotal trials supporting the US Food and Drug Administration (FDA) approval of SRDs treatments and to assess the quality of reporting. Methods We reviewed the pivotal trials supporting the approval of SRD indications by FDA since July 2013 to assess the use of PROs, including specific PRO measures (PROMs) and types of endpoints designated. Quality of PRO reporting was assessed according to a modified ISOQoL criteria. Results From July 1st, 2013, to June 30th, 2024, the FDA approved 43 new SRD indications based on 67 pivotal trials, with 58 trials included in the final analysis. PROs served as multiple types of endpoints in most trials. All 58 reviewed trials utilized PROs as secondary or exploratory endpoints. The numbers of trials that employed PROs as components of primary endpoints, co-primary endpoints, and key secondary endpoints, were 47(81.0%), 4(6.9%), 45(77.6%), respectively. Notably, the inclusion of PROs as components of composite primary endpoints or co-primary endpoints (100% vs. 8.3%, P < 0.001) and key secondary endpoints (93.5% vs. 16.7%, P < 0.001) were significantly higher in inflammatory arthritis compared to other SRDs. Regarding PROM types, 37 trials (63.8%) reported both generic and disease-specific PROMs, covering a broad range of domains. Quality of PRO reporting, influenced by disease type and the presence of additional PRO reports, was moderate to poor in 45 trials (81.8%). Key reporting elements, such as the PRO hypothesis, mode of PROMs completion, and extent and reasons for missing PRO data, were documented in fewer than 30% of the trials. Conclusion PROs significantly impact SRDs drug approval decisions, especially for inflammatory arthritis. However, the overall quality of PRO reporting in pivotal trials of SRDs is suboptimal and needs improvement. Our study provides a comprehensive summary of PRO application in SRDs trials, highlighting the need for strengthening PRO utilization in non-arthritis SRDs and improving PRO reporting quality in future studies.